1D model development and simulation of low-grade waste heat recovery from a marine engine - Bhandari, Varun (My University, 2021)
The increasing awareness about the effect of emission of CO2 into the atmosphere, as well as meeting the emission targets set by IMO (International Marine Orga- nization) by 2050 results in a continuous need for improving efficiencies of marine engines. A large portion of the fuel's chemical energy is lost to the surroundings as heat, even in the most energy efficient engines. Waste heat recovery through a rankine cycle has emerged as a promising way to increasing the engine efficiency by utilizing the untapped availability of waste heat in the coolant systems as well as the exhaust of the engine. The highly transient nature of operation of an engine and depicting the heat transfer phenomenon in an ORC (Organic Rankine Cycle) accurately makes the represen- tation of an ORC through a mathematical model quite challenging. Based on the application, selection of the right working uid, equipment and control strategy is crucial for the performance of the ORC In this thesis, a Simulink based mathematical model of an ORC for waste heat recov- ery from a marine engine is built. The WHR (Waste Heat Recovery) model is built for transient operation. The model is run on a road cycle, built from actual field test data of a boat, to simulate its performance in actual operation of the marine vessel. Further, the performance of ORC with di erent working uids and different type of expanders is evaluated. And finally, a rough cost estimation of the ORC is done. The results from the project show that the refrigerant R1234ze(Z) is the most suit- able for engine coolant WHR application and turbine expander performs better than the volumetric expander. Lastly, as the scale of the ORC system increases, it becomes increasingly cost effective.